Wood Surface Finishing with Transparent Lacquers Intended for Indoor Use, and the Colour Resistance of These Surfaces during Accelerated Aging - Kúdela, Jozef; Sikora, Adam; Gondáš, Lukáš (Polymers, 2023)
This work evaluates the effects of accelerated aging on the discolouration of surface-treated spruce wood and oak wood coated with solvent-based polyurethane lacquers, and surface-treated spruce wood coated with water-based transparent coating systems. All concerned coating materials were intended for indoor use. It was also explored how the colour stability of spruce wood and oak wood surfaces treated with solvent-based polyurethane lacquers was affected by wood surface layer modifications with pigment or stain mordants applied before these lacquers. Another issue studied was how the lignin stabilizer admixed into the primer and pigments admixed into the top coating layers affected the stability of water-based coating systems on spruce. The experimental results showed that the accelerated aging process with a simulation of indoor conditions induced significant discolouration of wood surfaces coated with solvent-based polyurethane lacquers and water-based coating systems. There were also confirmed significant impacts of all the studied factors (wood species, lacquer/coating system type, lacquer modification, wood pre-treatment with pigment and stain mordants). The spruce wood surfaces coated with solvent-based polyurethane lacquers were less stable (ΔE = 10-19, dependent on the lacquer type) than the oak surfaces treated in the same ways (ΔE = 4-11). There were also confirmed significant impacts of the particular surface treatment on the colour stability as well as significant impacts of wood surface pre-treatment with pigment and stain mordants (ΔE = 4-17-for spruce wood, and ΔE = 5.5-13-for oak wood). In the case of water-based lacquers, the ΔE values ranged between 3 and 11 (according to the coating system type). The results show that an appropriate UV absorbent combined with an appropriate lignin stabilizer and pigment mordant may enable attaining the required colour stability for a given surface treatment applied on a given wood species.
Keywords: oak; pigment mordants; accelerated ageing; solvent-based polyurethane lacquers; spruce wood; water-based lacquers; surface treatment